The need to build on international experiences to advance the tourism sector in Algeria (Journal of Economic Additions, 2020)
This study aims to research the topic of global tourism and its basic indicators with a focus on lessons learned to promote the tourism sector in Algeria, We have  followed  the descriptive analytical approach that we have supported by field data monitored by international bodies, where this research has concluded to develop a proposed model for the advancement of the tourism sector in Algeria by the light of positive indicators and successful international experiences of the field of international tourism. Keywords: Tourism; development; investment; tourist ; Economy.Jel Classification Codes: L83